PENGEMBANGAN STRUKTUR ORGANISASI KURIKULUM DALAM RANGKA MEMBANGUN SEKOLAH UNGGUL - Lusiman Lusiman; Ali Wafa; Eka Diana (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
The development of the curriculum as a scientific discipline today is growing very rapidly, both terrorist and practical. If in the past the traditional curriculum was more focused on subjects with a pouring system, now the curriculum is more oriented to new dimensions, such as life skills, self-development, economic and industrial development, globalization era with various problems, politics, even in practice it has touched the technological dimension especially information and communication technology. The role of the curriculum system is very important because there are two important reasons. First, the curriculum as a tool to achieve educational goals, therefore the curriculum must really exist. Second, the curriculum is basically the science of the nation's educational process so that it is meaningful for its life, both as individuals, family members, community members, and disciplines that must be studied by people involved in education, especially those who are prospective teachers or have become teachers.